Avaliação cardiovascular em pessoas vivendo com HIV/AIDS matriculadas na URE-DIPE-PA no período de outubro de 2017 - VICENTE, Gustavo de Souza (2019)
Introduction: AIDS that was previously an acute disease was considered a chronic disease, but the increase in survival of these patients exposed them to the degenerative effects of the disease and the consequent emergence of non-infectious HIV-related comorbidities and the toxicity of antiretroviral treatment among these cardiovascular diseases. These increases in cardiovascular events in PLHA are related to a number of factors, including the chronic inflammatory state of this disease, the use of HAART, especially the use of protease inhibitors that are responsible for the potentiation of dyslipidemia in these patients , not to mention metabolic changes and a more "atherogenic" state in this population. Metabolic changes favor the emergence of insulin resistance, which represents an important risk factor for triggering systemic arterial hypertension. This insulin resistance, hypertension, changes in lipid profile and increased waist circumference represent a clinical condition known as the metabolic syndrome, which is an important risk factor for cardiovascular disease. Objective: To describe the main cardiovascular risk factors in PLHA using the Framingham score, to demonstrate the PLHA lipid profile in the ERU-DIPE-PA, to identify the main antiretrovirals used by the PLHA in the ERU-DIPE-PA, to describe the socio-demographic and the PLHA living habits. Methods: A cross-sectional, descriptive-analytical study was carried out in October 2017, with 46 PLHA individuals enrolled and followed up in ERU-DIPE-PA. The present project was approved by the Research Ethics Committee with Human Beings of the Health Sciences Institute of the Federal University of Pará (ICS-UFPA), Opinion No. 112753/2017; CAE: 77367917.5.0000.0018. Results: We evaluated 46 patients enrolled in the ERU-DIPE-PA. The percentage of the male gender (63.1%) was higher than the female (36.9), the age group with the highest frequency was between 40-44 years (26.1%), followed by the following age group 20-34 years (21.7%) and over 50 years (21.7%). There is a predominance of single people with (80.5%), followed by those married (10, 8%). Those with income up to two minimum wages were the ones with the most diagnoses (82.6%), followed by those with income between 3 and 5 minimum wages (14.9%) and those with income above six minimum wages (2.1%). Most of the individuals (50%) come from Belém and the metropolitan region, and individuals from the interior of the state were very expressive (43.4%). There is a higher percentage among the individuals with a high school degree (42.6%), followed by incomplete (34%), and the upper level were considered low with only (4, 3%) completed or are in progress. Conclusion: There was a predominance of males, aged between 40 and 44 years old, coming from the metropolitan area of Belém. Among the professions, there was prevalence of autonomous professionals, domestic, hairdresser and students. The altered HDL-cholesterol, triglyceride levels above normal, sedentary lifestyle and inadequate eating habits were the most frequent findings among PLHA.